2016
DOI: 10.1186/s10194-016-0664-3
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of messenger molecules and receptors in rat and human sphenopalatine ganglion indicating therapeutic targets

Abstract: BackgroundMigraine and Cluster Headache (CH) are two primary headaches with severe disease burden. The disease expression and the mechanisms involved are poorly known. In some attacks of migraine and in most attacks of CH, there is a release of vasoactive intestinal peptide (VIP) originating from parasympathetic cranial ganglia such as the sphenopalatine ganglion (SPG). Patients suffering from these diseases are often deprived of effective drugs. The aim of the study was to examine the localization of the botu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Another argument testifying the SPG role in pathophysiology of migraine is the enrichment of SPG, besides ACh, with the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP), as one of the main migraine mediators ( 8 , 9 ). Finally, in a recent work ( 10 ) it has been suggested that parasympathetic mechanisms, in particular the neurotransmitters expressed in SPG, are important for induction of cluster headache.…”
Section: Resultsmentioning
confidence: 99%
“…Another argument testifying the SPG role in pathophysiology of migraine is the enrichment of SPG, besides ACh, with the neuropeptide pituitary adenylate cyclase-activating polypeptide (PACAP), as one of the main migraine mediators ( 8 , 9 ). Finally, in a recent work ( 10 ) it has been suggested that parasympathetic mechanisms, in particular the neurotransmitters expressed in SPG, are important for induction of cluster headache.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2 radiofrequency modalities normally used in management of headache and facial pain conditions, radiofrequency lesioning can result in permanent or more often temporary hypoesthesia, dysesthesia, or deafferentation pain in the palate, maxilla, or posterior pharynx 14 . Conversely PRF applies a non‐neurodestructive electrical field that has been able to increase early gene expression of c‐Fos immunoreactivity in some neurons without denaturing proteins, suggesting that PRF modulates nervous tissue rather than directly damaging it 18,19 . To avoid potentially permanent side effects and in view of the fact that radiofrequency ablation of the SPG does not seem to be superior to SPG‐PRF in the treatment of CH, 13 the latter modality was used in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PACAP1-38 has been suggested in the ethiopathology of migraine, though some aspects are still yet to be revealed [128][129][130]. PACAP1-38 was detected in the TG [131], in the TNC [132], and also in the parasympathetic otic and sphenopalatine ganglia [133][134]. Elevated levels of PACAP were found in the interictal phase compared to the ictal phase in migraine patients and also in cluster headache attacks [135][136].…”
Section: Pituitary Adenylate Cyclase-activating Polypeptide (Pacap)mentioning
confidence: 99%